PENGARUH PENERAPAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - Usep Suwanjal (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Critical thinking skills of mathematics mastered by students is very important, especially in the competition of globalitation era. An approach that can improve both of them is contextual approach in learning. This research aims are to determine: The Improvement of students' critical thinking skills between the class which used contextual approach in learning and the one which used conventional learning. Quasi-experiment methods was used in the research and the design was